The determinants of adolescents’ deviant behaviours - Enache, Rodica Gabriela; Bîrsan, Sorina (Technium Social Sciences Journal, 2021)
Deviance is a fundamental social construct because the members of society interpret its meaning and attribute its meaning to it. In our research we described the causes that determine deviance (juvenile delinquency): internal/individual causes and external / social causes. The purpose of the research was to make a comparison between the psychological problems of institutionalized adolescents with deviant behaviour and those of non-institutionalized adolescents with deviant behaviour.